(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The Celtiberian inscriptions, published after IV Botorrita bronze, especially the Inhiesta lead, have provided us a number of new verbal forms. In this paper I have put together all these forms, as well as others that have arisen from new readings and interpretations of the inscriptions already known, and tried to establish their mutual relations, to determine possible minimum paradigms and a cast of documented verbal categories.